2013
DOI: 10.1183/09031936.00012813
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of new-onset asthma and nasal allergy by skin prick test and RAST in a cohort of adults

Abstract: Limited information exists regarding the incidence and predictors of asthma and nasal allergy in adulthood. We determined the incidence rate of asthma and nasal allergy in adults and assessed the predictive value of skin prick tests (SPTs) and radioallergosorbent tests (RASTs) for these two outcomes.Two German centres involved in the European Community Respiratory Health Survey conducted a follow-up assessment in 2012 of the baseline participants (1185 adults aged 21-47 years assessed in 1990). The predictive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 30 publications
6
12
0
Order By: Relevance
“…A similar study in German adults aged 25‐74 years also showed that allergic sensitization to outdoor allergens was a predictor for the development of allergic rhinitis during a 10‐year period . Furthermore, in a German study, a cohort of 21‐47 years olds was followed up after 20 years, and here, new nasal allergy was predicted by eczema, any positive SPT or specific IgE . A positive reaction to birch pollen was the strongest predictor for new‐onset nasal allergy.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…A similar study in German adults aged 25‐74 years also showed that allergic sensitization to outdoor allergens was a predictor for the development of allergic rhinitis during a 10‐year period . Furthermore, in a German study, a cohort of 21‐47 years olds was followed up after 20 years, and here, new nasal allergy was predicted by eczema, any positive SPT or specific IgE . A positive reaction to birch pollen was the strongest predictor for new‐onset nasal allergy.…”
Section: Discussionsupporting
confidence: 54%
“…Comparing results from different studies can be challenging due to different definitions, diagnostic criteria and study designs and measurements of sensitization are not always included. Several prospective, population‐based cohort studies have evaluated time trends of allergic sensitization and atopic diseases during childhood and a few have been performed during adulthood . However, studies prospectively evaluating the course of allergic sensitization and atopic diseases from childhood or adolescence to adulthood are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Allergic rhino-conjunctivitis is a well-known risk factor for asthma [ 4 , 17 , 19 , 21 ] and is a reasonable proxy for allergic sensitisation, at least among younger and middle-aged adults [ 21 ]. In the current study it was the strongest and most stable risk factor for asthma, which further strengthens the causality of the association.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity of each diagnostic test were obtained from five different published articles [7][8][9][10][11] (Table 1). Karrasch et al 7 assessed FeNO accuracy for making the diagnosis of asthma by conducting a systematic review and diagnostic meta-analysis of 26 different studies, which account for a total of 4518 participants.…”
Section: Data Sourcesmentioning
confidence: 99%
“…11 evaluated the diagnostic utility of skin prick tests (SPTs) and radioallergosorbent tests (RASTs) in 1185 patients during 20 years.…”
mentioning
confidence: 99%